(untitled) (International Journal of Engineering and Computer Science, 2018)
Machine tools have imperative role in technology advances, escalating productivity and accuracy. However heat generated in machine tool results in thermal error that affects the machining precision and productivity. In machine tool the heat is generated due to internal and external heat sources. A spindle is the main internal source of heat generation. This heat can be dissipated by efficient cooling techniques. We have focused on forced cooling, conventional cooling and thermoelectric cooling techniques. This paper intended to provide investigational information about different cooling techniques for spindle of machine tool